Exploring Students’ Perception and Use of Movie Clips to Enhance Students’ Participation in English Classroom - Panjaitan, Bontor Rusmida; Hasibuan, Monalisa Irmayanti (Journal of English Teaching and Learning Issues, 2022)
Learning a foreign language is not easy and requires a lot of effort. A teacher must be able to give maximum effort in teaching in the classroom and one way is by using ICT. The aim of this study is to find out whether using movie clips can increase students’ participation in online English classes and what factors caused students to be active in online class. The design of this research is classroom action research (CAR) with the subject of the research was 35 students of class X MIPA 6 at senior high school in Tualang. This research was conducted in one cycle consisting of 5 online class meetings that used movie clips with different genres. From the results of research using observation sheets and interviews with students, it can be seen that students feel more enjoy, enthusiastic, curious in English class so that it affects their activity and participation in class, as most people, basically, like to watch movies. The aim of the interview is to explore students' opinions about what factors are their challenges in online learning. Most students say that they have problems with limited internet quota, unstable internet network, inadequate economy, and even boredom with assignments and deadlines during online learning. In this case the teacher must be able to find alternative solutions for online classes to make students not bored and enjoy the learning environment created by the teacher.